'Nay, Don't Teach Me Morals' - Das KG; Bharath Raj J (Journal of All India Institute of Speech and Hearing, 1971)
Miss T, an young girl of 15 years, fair complexioned and attractive was brought for consultation for certain psychological problems. As an orphan she was picked up at the age of 5 months and brought up by a Mother lovingly. Her unlawful parentage was traced to an Indian mother and an English father. She grew up in the restrained atmosphere of a convent